Treasury Bills and/Or Central Bank Bills for Absorbing Surplus Liquidity : The Main Considerations - Nyawata, Obert (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses the challenging question of whether central banks should use treasury bills or central bank bills for draining excess liquidity in the banking system. While recognizing that there are practical reasons for using central bank bills, the paper argues that treasury bills are the first best option especially because positive externalities for the financial sector and the rest of the economy. However, the main considerations in the choice should be: (i) operational independence for the central bank; (ii) market development; and (iii) the strengthening of the transmission of monetary policy impulses.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet